Optimization of Packaging Process Parameters Using Combined Taguchi Method-present Worth Method/Inflationary Factor Validated - Oke, S.A.; Fagbolagun, I.O. (Universitas Atma Jaya Yogyakarta, 2020)
In a previous article, the packaging optimization literature illustrated how to optimize the packaging parameters using the classical Taguchi approach. Notwithstanding, it is compelling to bridge the gap created in the article for further advancement. Thus, this paper contributes to expanding scholarship regarding the area. The paper targets the Taguchi methodical optimization literature in which several scores of research across engineering disciplines and beyond have been undertaken. At present, evaluation using the Taguchi method often stops at the determination of the optimal settings from the response table through a chain of steps from factor-level selection, orthogonal array choice, signal-to-noise determination, and response table evaluation to emerge the optimal parameters. There is no information on the economic aspects of the parameters, yet processes are expected to be sustainable while economic factors play a central role. A novel idea of the present work is introduced where the interest rate and inflationary factor with levels are used to determine the economic strength of each parameter through ranking. Data was collected from a brewery process, and literature data concerning cold arc welding parametric evaluation was used. The outcome demonstrates the workability of the method in the packaging plant and cold arc welding process. The work is useful for packaging managers and welding engineers for planning purposes.